Measurement of straightness and verticality of sheet piling - Kokoszka, Wanda; Ochab, Piotr; Gardzińska, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Sheet piling is commonly used in various areas of special construction. Embedded in the ground before carrying out excavation works, sheet piling constitutes an enclosure and protection for the designed excavation. It is a temporary enclosure and protection for excavations made for communication structures, launch shafts built for microtunnel construction, etc.
Keywords: special construction; technological chamber; sheet piling; measurement of straightness; verticality measurement; accuracy analysis; konstrukcja specjalna; komora technologiczna; ścianki szczelne; pomiar prostoliniowości; pomiar pionowości; analiza dokładności